2000
DOI: 10.3168/jds.s0022-0302(00)75148-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Roasting Nonlinted Whole Cottonseed on Milk Production by Dairy Cows

Abstract: This study was conducted to examine the effect of roasting nonlinted whole cottonseed on ruminal crude protein (CP) degradability and performance in high-yielding dairy cows. Multiparous Israeli Holstein-Friesian cows (parity average 2.5+/-1.5; n = 132) with 571+/-65 kg of body weight (BW), 107+/-48 d in milk (DIM), and 37+/-5.8 kg of milk yield/d were used in the study. Cows were divided into two dietary treatment groups according to their BW, DIM, and milk production. The two diets were similar in CP, net en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…However, we observed that the milk protein was increased when cows were fed delinted and extruded WCS (P<0.05), which was consistent with some previous reports (Mabjeesh et al, 2000;Reveneau et al, 2005). This can be explained that microbial protein synthesis was improved when cows were fed processing WCS, resulting in an increase of protein fl ow in the small intestine.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…However, we observed that the milk protein was increased when cows were fed delinted and extruded WCS (P<0.05), which was consistent with some previous reports (Mabjeesh et al, 2000;Reveneau et al, 2005). This can be explained that microbial protein synthesis was improved when cows were fed processing WCS, resulting in an increase of protein fl ow in the small intestine.…”
Section: Resultssupporting
confidence: 91%
“…Johnson et al (2002) reported that MUN was increased when cows were fed with oilseed. It is likely that free oil of extruded WCS has negative effect on rumen microbial protein and more nitrogen is absorbed across the ruminal wall and synthesized into MUN by the mammary gland (Mabjeesh et al, 2000). Milk lactose was not affected by the dietary factors (P>0.05).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Extrusion of the cottonseed frees the seed oil and is likely associated with negative effects on rumen microbial growth (Mabjeesh et al, 2000) and NH 3 -N utilization in rumen.…”
Section: Resultsmentioning
confidence: 99%